The new Libertad Public Market revitalizing our urban spaces - Aguirre, Angelo Gabriel P. (College of Architecture, University of the Philippines Diliman, 2019)
Our public markets have always served as centers of local culinary heritage, offering the best and freshest of what each region, city, or town has to offer. Sadly, more and more of your market structures are falling into despair and are losing customers to large chains such as Save More and Pure Gold. This project aims to explore how we can rethink our public markets as important urban spaces and strengthen their identity as centers of a place's culinary heritage. With this in mind, the project locates itself in Bacolod City, well known for its strong food culture and proximity to centers of food production. The Libertad Public Market is reimagined and redesigned based on how the main problem previously mentioned manifests itself in this specific market in Bacolod. On site observation and interviews with current stake holders were used to guide the entire design process. The resulting project then becomes an example of how site-specific, user-based, design can help strengthen our markets and ensure their survival in our urban landscapes in the coming years.